A method for manufacturing a high wear-resistant composite swing hammer head

Through microwave curing process and extrusion casting method, a reactive interface is formed, which solves the problem of poor bonding performance of ceramic particles and metal composite hammer heads, and significantly improves the wear resistance and service life of the hammer heads.

CN116251941BActive Publication Date: 2025-02-07NANTONG INST OF TECH

Patent Information

Application Number
CN202310181966.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-01
Publication Date
2025-02-07
Estimated Expiration
2043-03-01

AI Technical Summary

Technical Problem

The existing ceramic particles and metal composite hammer head have poor bonding performance during the infiltration process, and cracks are easily generated at the interface after heat treatment, resulting in the ceramic particles being easily shedded and have a short life.

Method used

By adopting microwave curing technology and extrusion casting method, the surface of the ceramic particles is coated with boron carbide ceramic powder and mixed with NiCrBSi powder and sodium silicate solution to form a honeycomb ceramic prefabricated body, and high-pressure impregnation is carried out in combination with high chromium cast iron iron. Form a reactive interface.

Benefits of technology

It significantly improves the bonding performance of ceramic particles and high chromium cast iron matrix, extends the service life of the hammer head, and improves the wear resistance to 3-4 times.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116251941B_ABST
    Figure CN116251941B_ABST
Patent Text Reader

Abstract

The invention discloses a method for manufacturing a high-wear-resistant composite swing hammer head, which comprises the following steps: washing and drying ceramic particles with an oxalic acid solution, uniformly mixing boron carbide ceramic powder and an alcohol adhesive in proportion into a slurry, and drying to remove the alcohol adhesive; then mixing the ceramic particles with NiCrBSi powder and a sodium silicate solution and filling the mixture into a honeycomb mold, taking the mixture out after microwave curing, thereby obtaining a honeycomb ceramic preform with high strength at room temperature, wherein a conical preformed hole is formed on the honeycomb ceramic preform, placing the honeycomb ceramic preform into a casting cavity of a swing hammer head metal mold, and then pouring molten high-chromium cast iron into a runner of the casting mold, wherein the high-chromium cast iron water infiltrates into gaps between ceramic preform particles under high pressure to form a reactive interface, thereby obtaining a high-wear-resistant composite swing hammer head. The method can manufacture a composite swing hammer head with a reactive interface and high wear resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ceramic swing hammer manufacturing, and particularly relates to a method for manufacturing a high-wear-resistant composite swing hammer hammer head. Background Art

[0002] The hammer crusher's hammer is very easy to wear and tear when it strikes the material. Its working surface is generally 15 to 20 days old. Under bad working conditions, its life span is only about 7 days. Frequent shutdowns for maintenance seriously affect production efficiency. The common materials of hammer heads on the market are high manganese steel, carbon steel / high chromium cast iron bimetallic composite, and titanium carbide rod inlaid high manganese steel. In recent years, researchers have taken ceramic particle reinforced metal composite hammer heads as a new research and development direction.

[0003] However, due to the poor wettability of ceramic particles and metals, capillary resistance is the main resistance to metal infiltration. When the infiltration power is insufficient, it is difficult to overcome the infiltration resistance, and the infiltration effect is poor, resulting in poor bonding between ceramic particles and metal. In addition, during the heat treatment of the composite hammer head, due to the mismatch in thermal expansion coefficients between the honeycomb ceramic preform and the metal matrix, cracks are easily generated at the interface between the honeycomb ceramic preform and the metal matrix, and ceramic particles are easy to fall off during equipment operation, which seriously restricts the industrialization process of ceramic composite swing hammer heads.

[0004] In view of the current problems of poor wettability between base metal and ceramic particles, cracks on the interface after heat treatment, easy shedding of ceramic particles and short life, the present invention provides a method for manufacturing a composite swing hammer head with a reactive interface and high wear resistance. Summary of the invention

[0005] Purpose of the invention: In order to overcome the deficiencies in the prior art, the present invention provides a method for manufacturing a highly wear-resistant composite swing hammer head, which can manufacture a composite swing hammer head with a reactive interface and high wear resistance.

[0006] Technical solution: To achieve the above purpose, the technical solution of the present invention is as follows:

[0007] A method for manufacturing a highly wear-resistant composite swing hammer head comprises the following steps:

[0008] S1: Ceramic particles with a particle size of 10 to 16 mesh are soaked in oxalic acid solution, vibrated and cleaned, and then placed in a drying oven for drying until the moisture on the surface of the ceramic particles is removed;

[0009] S2: 300-400 mesh boron carbide ceramic powder and alcohol adhesive are uniformly mixed in proportion to form a slurry;

[0010] S3: coating the slurry prepared in step S2 on the surface of the dried ceramic particles, and then drying them in a drying oven to remove the alcohol adhesive;

[0011] S4: the ceramic particles prepared in step S3 are uniformly mixed with NiCrBSi powder and sodium silicate solution in proportion, and the mixed mixture is filled into a honeycomb mold, and then the whole is put into a microwave oven for microwave curing for a predetermined time and then taken out to obtain a honeycomb ceramic preform with high strength at room temperature, and the honeycomb ceramic preform is formed with conical preformed holes;

[0012] S5: preheating the honeycomb ceramic preform to a preset temperature and then placing it into a casting cavity of a swing hammer metal mold, with the side with a larger preformed hole diameter close to the end face of the swing hammer;

[0013] S6: installing the entire forming mold device of step S5 on a press, then pouring molten high-chromium cast iron into the pouring channel of the casting mold, and then closing the upper and lower molds and locking them under high pressure;

[0014] S7: Under high pressure, the guide device is pushed to squeeze the high chromium cast iron liquid in the runner into the casting cavity of the swing hammer head mold, and the high chromium cast iron liquid is infiltrated into the gaps between the ceramic preform particles under high pressure to form a reactive interface, and the pressure is maintained until solidification is completed, and then the guide device is removed, and the mold is opened to eject the high wear-resistant composite swing hammer head blank;

[0015] S8: Clean and grind the composite swing hammer head blank, and then put it into a heat treatment furnace for quenching and tempering heat treatment to obtain a highly wear-resistant composite swing hammer head.

[0016] Furthermore, in step S2, the amount of boron carbide ceramic powder added is 6% to 10% of the mass of the ceramic particles, and the amount of alcohol adhesive added is 8% to 12% of the mass of the ceramic particles.

[0017] Furthermore, in step S4, the amount of NiCrBSi powder added is 3% to 6% of the mass of the ceramic particles, and the amount of sodium silicate solution added is 6% to 9% of the mass of the ceramic particles.

[0018] Furthermore, the ceramic particles in step S1 are composed of aluminum oxide, zirconium oxide or zirconium corundum.

[0019] Furthermore, the mass content of oxalic acid in the oxalic acid solution in step S1 is 10% to 15%.

[0020] Furthermore, the alcohol adhesive in step S2 is ethanol, ethylene glycol or polyvinyl alcohol.

[0021] Furthermore, in step S4, the particle size of the NiCrBSi powder is 300-400 mesh.

[0022] Furthermore, in step S6, the high chromium cast iron composition is BTMCr15, BTMCr20 or BTMCr26.

[0023] Furthermore, the preformed holes of the honeycomb ceramic preform have a conical structure, and the taper of the preformed holes is 3° to 6°.

[0024] Furthermore, the honeycomb ceramic preform is arranged on a side of the swing hammer away from the hammer handle, and the thickness of the honeycomb ceramic preform is 25 to 40 mm.

[0025] Beneficial effects: The present invention has the following advantages:

[0026] (1) Compared with the previous drying oven heat curing method, the microwave curing method can shorten the curing time of the honeycomb ceramic preform from several hours to several minutes, greatly improving the production efficiency. In addition, due to the short curing time, it can prevent the ceramic particles from sinking due to gravity, ensuring the uniform distribution of the ceramic particles.

[0027] (2) After microwave curing of the sodium silicate binder, an amorphous phase appears. Due to its isotropy, the amorphous phase can better connect the ceramic particles. The gaps between the irregular ceramic particles are almost completely filled with the binder, so that the entire particle is wrapped by the binder. The bonding strength is greatly improved compared to thermal curing. At the same time, the amorphous phase itself has excellent wear resistance.

[0028] (3) The use of extrusion casting infiltration method greatly increases the infiltration power of high chromium cast iron water, making the high chromium cast iron water infiltrate deeper and more fully, which is beneficial to the improvement of the interface bonding performance between ceramic particles and high chromium cast iron matrix.

[0029] (4) The hole type of the honeycomb ceramic preform adopts a conical structure, which can make the high chromium cast iron shrink and infiltrate during the liquid and solid shrinkage process. At the same time, because the preform hole has a certain slope, the compressive stress of the high chromium metal matrix in the hole on the ceramic particles after heat treatment can make the bonding stronger, thus solving the problem of micro cracks at the interface between the high chromium metal matrix and the ceramic particles after heat treatment due to the different thermal expansion coefficients.

[0030] (5) The surface of the ceramic particles is preferentially coated with boron carbide ceramic powder, which can achieve sufficient interfacial reaction bonding under the high temperature of pouring high-chromium cast iron molten iron, react with the surface of the ceramic particles to form an Al2O3·B2O3 reactive interface, and form a boron-iron alloy with the metal matrix, thereby improving the problem of weak bonding between the ceramic and the metal matrix. At the same time, NiCrBSi has a low melting point and good fluidity, which can further induce the infiltration of the high-chromium cast iron matrix to form an infiltration channel to form a good metallurgical bond.

[0031] (6) The present invention can solve the problem of poor interface bonding performance between ceramic particles and high chromium cast iron matrix from the aspects of hole structure, microwave curing process, extrusion casting process, ceramic preform composition, etc., and the life of the wear-resistant swing hammer head can be increased to 3-4 times the original. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 It is a schematic diagram of the manufacturing method of the present invention;

[0033] Figure 2 A schematic diagram of the structure of a high wear-resistant composite swing hammer hammer head according to an embodiment of the present invention;

[0034] Figure 3 A schematic diagram of the structure of a honeycomb ceramic preform according to an embodiment of the present invention;

[0035] Figure 4 A cross-sectional view of a honeycomb ceramic preform structure according to an embodiment of the present invention;

[0036] Figure 5 This is the actual picture of the working surface of the composite swing hammer after color flaw detection. DETAILED DESCRIPTION

[0037] The present invention will be further described below in conjunction with the accompanying drawings.

[0038] As attached Figure 1 As shown, a method for manufacturing a high wear-resistant composite swing hammer head comprises the following steps:

[0039] S1: soaking and vibrating ceramic particles with a particle size of 10 to 16 meshes in an oxalic acid solution, and then drying them in a drying oven at 200 to 250° C. for 5 to 10 hours until the moisture on the surface of the ceramic particles is removed;

[0040] S2: 300-400 mesh boron carbide ceramic powder and alcohol adhesive are uniformly mixed in proportion to form a slurry; wherein the amount of boron carbide ceramic powder added is 6%-10% of the mass of the ceramic particles, and the amount of alcohol adhesive added is 8%-12% of the mass of the ceramic particles;

[0041] S3: coating the slurry prepared in step S2 on the surface of the dried ceramic particles, and then drying them in a drying oven at 250-350° C. to remove the alcohol adhesive;

[0042] S4: The ceramic particles obtained in step S3 are mixed with NiCrBSi powder and sodium silicate solution in proportion, wherein the amount of NiCrBSi powder added is 3% to 6% of the mass of the ceramic particles, and the amount of sodium silicate solution added is 6% to 9% of the mass of the ceramic particles. The mixed mixture is filled into a honeycomb mold with a conical honeycomb column, slightly compacted, with a taper of 3-6°, and then the whole is placed in a microwave oven for microwave curing for a predetermined time of 60 to 70 seconds and then taken out to obtain a honeycomb ceramic preform with high strength at room temperature, and the honeycomb ceramic preform is provided with conical preformed holes formed by the conical honeycomb column;

[0043] By adopting microwave curing method, compared with the previous drying oven heat curing method, the curing time of honeycomb ceramic preform is shortened from several hours to several minutes, and the production efficiency is greatly improved. In addition, due to the short curing time, the sinking of ceramic particles caused by gravity can be prevented, ensuring the uniform distribution of ceramic particles.

[0044] After microwave curing of the sodium silicate binder, an amorphous phase appears. Due to its isotropy, the amorphous phase can better connect the ceramic particles. The gaps between the irregular ceramic particles are almost completely filled with the binder, so that the entire particle is wrapped by the binder. The bonding strength is greatly improved compared to thermal curing. At the same time, the amorphous phase itself has excellent wear resistance.

[0045] The hole type of the honeycomb ceramic preform adopts a conical structure. The hole type structure of the honeycomb ceramic preform is a conical structure, and the taper of the preformed hole is 3° to 6°. This structure can make the high chromium cast iron shrink and infiltrate the metal liquid during the liquid and solid shrinkage process. At the same time, because there is a certain slope in the preform hole, the compressive stress of the high chromium metal matrix in the hole on the ceramic particles after heat treatment can make the combination stronger, solving the problem of micro cracks after heat treatment caused by different thermal expansion coefficients at the interface between the high chromium metal matrix and the ceramic particles.

[0046] The surface of the ceramic particles is preferentially coated with boron carbide ceramic powder, which can achieve sufficient interface reaction bonding under high temperature of pouring high chromium cast iron molten iron, react with the surface of the ceramic particles to form Al2O3·B2O3 reactive interface, and form boron iron alloy with the metal matrix, thereby improving the problem of weak bonding between the ceramic and the metal matrix; at the same time, NiCrBSi has a low melting point and good fluidity, which can further induce the infiltration of the high chromium cast iron matrix to form an infiltration channel to form a good metallurgical bond.

[0047] S5: preheating the honeycomb ceramic preform to a preset temperature of 350-400° C. and placing it into a casting cavity of a swing hammer metal mold, with the side with a larger preformed hole diameter close to the end face of the swing hammer;

[0048] S6: installing the entire forming mold device of step S5 on a press, then pouring molten high chromium cast iron at 1450-1500° C. into the pouring channel of the casting mold, and then closing the upper and lower molds and locking them under a high pressure of 100-120 MPa;

[0049] S7: Under a high pressure of 110-130 MPa, the guide device is pushed to squeeze the high chromium cast iron water in the runner into the casting cavity of the swing hammer head mold. Under the high pressure, the high chromium cast iron water infiltrates into the gaps between the ceramic preform particles to form a reactive interface. After the pressure is maintained until solidification is completed, the guide device is removed, and the mold is opened to eject the high wear-resistant composite swing hammer head blank. The use of the extrusion casting method greatly increases the infiltration power of the high chromium cast iron water, making the high chromium cast iron water infiltrate deeper and more fully, which is beneficial to the improvement of the interface bonding performance between the ceramic particles and the high chromium cast iron matrix.

[0050] S8: Clean and grind the composite swing hammer head blank, then put it into a heat treatment furnace for quenching at 970-1040° C. and tempering at 400-440° C. to obtain a 59-62HRC high wear-resistant composite swing hammer head.

[0051] The ceramic particles in step S1 are composed of aluminum oxide, zirconium oxide or zirconium corundum.

[0052] The mass content of oxalic acid in the oxalic acid solution in step S1 is 10% to 15%.

[0053] The alcohol adhesive in step S2 is ethanol, ethylene glycol or polyvinyl alcohol, and the alcohol can be released at high temperature.

[0054] In step S4, the particle size of NiCrBSi powder is 300-400 mesh.

[0055] In step S6, the high chromium cast iron composition is BTMCr15, BTMCr20 or BTMCr26.

[0056] The honeycomb ceramic preform is arranged on a side of the swing hammer away from the hammer handle. The honeycomb ceramic preform has a thickness of 25 to 40 mm and has high hardness and good bonding performance.

[0057] The present invention is further described in detail below through 4 specific embodiments:

[0058] Embodiment 1:

[0059] S1. After soaking and vibrating the zirconium corundum particles with a particle size of 10 to 16 mesh in oxalic acid solution, the particles were placed in a drying oven and dried at 200°C for 5 hours to remove surface moisture;

[0060] S2, 300 mesh boron carbide ceramic powder and polyvinyl alcohol are uniformly mixed into a slurry, wherein the amount of boron carbide ceramic powder added is 6% of the mass of the zirconium corundum particles, and the amount of polyvinyl alcohol added is 8% of the mass of the zirconium corundum particles;

[0061] S3, coating the dried zirconium corundum particles with the slurry, and then drying them in a drying oven at 250° C. to remove the polyvinyl alcohol;

[0062] S4, the particles obtained in S3 are mixed evenly with NiCrBSi powder and sodium silicate solution, and filled into a honeycomb mold and slightly compacted, and then the whole is put into a microwave oven for microwave curing for 60 seconds and then taken out, the microwave curing power of the microwave oven is 1500W, and a honeycomb ceramic preform with high strength at room temperature is obtained; wherein, the amount of NiCrBSi powder added is 3% of the mass of the zirconium corundum particles, and the amount of sodium silicate solution added is 6% of the mass of the zirconium corundum particles;

[0063] S5, preheating the honeycomb ceramic preform to 350° C. and placing it into the casting cavity of the swing hammer metal mold, with the side of the preform with a larger aperture close to the end face of the swing hammer;

[0064] S6, install the whole set of forming mold device S5 on the press, then pour the molten BTMCr15 iron at 1450℃ into the pouring channel of the casting mold, and then close the upper and lower molds and lock them under a pressure of 100MPa;

[0065] S7. Under a pressure of 110 MPa, the guide device is pushed to squeeze the BTMCr15 molten iron in the runner into the casting cavity of the swing hammer head mold. Under high pressure, the BTMCr15 molten iron penetrates into the gaps between the preform particles to form a reactive interface. After the pressure is maintained until solidification is completed, the guide device is removed, and the mold is opened to eject the high wear-resistant composite swing hammer head blank.

[0066] S8. Clean and grind the composite swing hammer head blank, then put it into a heat treatment furnace for quenching at 980° C. and tempering at 400° C. to obtain a high wear-resistant composite swing hammer head with a base hardness of 59HRC.

[0067] Embodiment 2:

[0068] S1. After soaking and vibrating zirconium oxide particles with a particle size of 10 to 16 mesh in oxalic acid solution, the particles were placed in a drying oven and dried at 220° C. for 6 hours to remove surface moisture;

[0069] S2, uniformly mixing 350 mesh boron carbide ceramic powder and ethanol into a slurry, wherein the amount of boron carbide ceramic powder added is 7% of the mass of the zirconium oxide particles, and the amount of ethanol added is 9% of the mass of the zirconium oxide particles;

[0070] S3, coating the entire surface of the dried zirconium oxide particles with the slurry, and then drying in a drying oven at 260° C. to remove ethanol;

[0071] S4, the particles obtained in S3 are mixed evenly with NiCrBSi powder and sodium silicate solution, and filled into a honeycomb mold and slightly compacted, and then the whole is put into a microwave oven for microwave curing for 65 seconds and then taken out, the microwave curing power of the microwave oven is 1600W, and a honeycomb ceramic preform with high strength at room temperature is obtained; wherein, the amount of NiCrBSi powder added is 4% of the mass of the zirconium oxide particles, and the amount of sodium silicate solution added is 7% of the mass of the zirconium oxide particles;

[0072] S5, preheating the honeycomb ceramic preform to 380° C. and placing it into the casting cavity of the swing hammer metal mold, with the side of the preform with a larger aperture close to the end face of the swing hammer;

[0073] S6, install the whole set of forming mold device S5 on the press, then pour the molten BTMCr20 iron at 1460℃ into the pouring channel of the casting mold, and then close the upper and lower molds and lock them under a pressure of 110MPa;

[0074] S7, under a pressure of 120 MPa, push the guide device to squeeze the BTMCr20 molten iron in the runner into the casting cavity of the swing hammer head mold, and the BTMCr20 molten iron infiltrates into the gaps between the preform particles under high pressure to form a reactive interface, maintain the pressure until solidification is completed, remove the guide device, open the mold and eject the high wear-resistant composite swing hammer head blank;

[0075] S8. Clean and grind the composite swing hammer head blank, then put it into a heat treatment furnace for quenching at 990° C. and tempering heat treatment at 410° C. to obtain a high wear-resistant composite swing hammer head with a base hardness of 59.7HRC.

[0076] Embodiment 3:

[0077] S1. After the alumina particles with a particle size of 10 to 16 mesh are soaked in oxalic acid solution and vibrated to clean, they are placed in a drying oven and dried at 250° C. for 8 hours to remove surface moisture;

[0078] S2, uniformly mixing 400-mesh boron carbide ceramic powder and ethanol into a slurry, wherein the amount of boron carbide ceramic powder added is 8% of the mass of the alumina particles, and the amount of ethanol added is 10% of the mass of the alumina particles;

[0079] S3, coating the entire surface of the dried alumina particles with the slurry, and then drying in a drying oven at 300° C. to remove ethanol;

[0080] S4, the particles obtained in S3 are mixed evenly with NiCrBSi powder and sodium silicate solution, and filled into a honeycomb mold and slightly compacted, and then the whole is put into a microwave oven for microwave curing for 68 seconds and then taken out, the microwave curing power of the microwave oven is 1700W, and a honeycomb ceramic preform with high strength at room temperature is obtained; wherein, the amount of NiCrBSi powder added is 5% of the mass of the zirconium oxide particles, and the amount of sodium silicate solution added is 8% of the mass of the zirconium oxide particles;

[0081] S5, preheating the honeycomb ceramic preform to 390° C. and placing it into a casting cavity of a swing hammer metal mold, with the side of the preform with a larger aperture close to the end face of the swing hammer;

[0082] S6, install the whole set of forming mold device S5 on the press, then pour the molten BTMCr26 iron at 1480℃ into the pouring channel of the casting mold, and then close the upper and lower molds and lock them under a pressure of 120MPa;

[0083] S7, under a pressure of 130 MPa, push the guide device to squeeze the BTMCr26 molten iron in the runner into the casting cavity of the swing hammer head mold, and the BTMCr26 molten iron infiltrates into the gaps between the preform particles under high pressure to form a reactive interface, maintain the pressure until solidification is completed, remove the guide device, open the mold and eject the high wear-resistant composite swing hammer head blank;

[0084] S8, cleaning and grinding the composite swing hammer head blank, and then putting it into a heat treatment furnace for quenching at 1010°C and tempering heat treatment at 430°C to obtain a high wear-resistant composite swing hammer head with a base hardness of 62HRC.

[0085] Embodiment 4:

[0086] S1. After soaking and vibrating the zirconium corundum particles with a particle size of 10 to 16 mesh in oxalic acid solution, the particles were placed in a drying oven and dried at 250° C. for 10 hours to remove surface moisture;

[0087] S2, uniformly mixing 400-mesh boron carbide ceramic powder and ethanol into a slurry, wherein the amount of boron carbide ceramic powder added is 10% of the mass of the zirconium corundum particles, and the amount of ethanol added is 12% of the mass of the zirconium corundum particles;

[0088] S3, coating the above slurry on the surface of the dried zirconium corundum particles, and then drying them in a drying oven at 350° C. to remove ethanol;

[0089] S4, the particles obtained in S3 are mixed evenly with NiCrBSi powder and sodium silicate solution, and filled into a honeycomb mold and slightly compacted, and then the whole is put into a microwave oven for microwave curing for 70 seconds and then taken out, the microwave curing power of the microwave oven is 1700W, and a honeycomb ceramic preform with high strength at room temperature is obtained; wherein, the amount of NiCrBSi powder added is 6% of the mass of the zirconium oxide particles, and the amount of sodium silicate solution added is 9% of the mass of the zirconium oxide particles;

[0090] S5, preheating the honeycomb ceramic preform to 400° C. and placing it into the casting cavity of the swing hammer metal mold, with the side of the preform with a larger aperture close to the end face of the swing hammer;

[0091] S6, install the whole set of forming mold device S5 on the press, then pour the molten BTMCr26 iron at 1450℃ into the pouring channel of the casting mold, and then close the upper and lower molds and lock them under a pressure of 120MPa;

[0092] S7, under a pressure of 120 MPa, push the guide device to squeeze the BTMCr26 molten iron in the runner into the casting cavity of the swing hammer head mold, and the BTMCr26 molten iron infiltrates into the gaps between the preform particles under high pressure to form a reactive interface, maintain the pressure until solidification is completed, remove the guide device, open the mold and eject the high wear-resistant composite swing hammer head blank;

[0093] S8. Clean and grind the composite swing hammer head blank, then put it into a heat treatment furnace for quenching at 1020° C. and tempering heat treatment at 440° C. to obtain a high wear-resistant composite swing hammer head with a base hardness of 60.6HRC.

[0094] Two groups of comparative examples were used for comparison with the four embodiments, wherein:

[0095] Comparative Example 1: Compared with Example 1, Example 2, Example 3 and Example 4, Comparative Example 1 does not contain a honeycomb ceramic composite preform, and the hammer head of the swing hammer is made of a high-chromium cast iron matrix material as a whole.

[0096] Comparative Example 2: A ceramic particle reinforced high chromium cast iron based composite swing hammer head prepared by a heat curing preform and a pressureless casting infiltration process.

[0097] The test structures of the above four embodiments and the test comparison of comparative example 1 and comparative example are shown in the following table:

[0098]

[0099] It can be seen from the above table that the three-body abrasive wear volume and hardness in Examples 1 to 4 are better than the high chromium cast iron substrate in Comparative Example 1, and the wear resistance is 4.2 times and 1.5 times that of Comparative Example 1 and Comparative Example 2, respectively. And the performance is the best with the ratio of Example 3.

[0100] The structure of the high wear-resistant composite swing hammer head finally obtained in the above embodiments 1 to 4 is as follows: Figures 2 to 4 As shown, the structure of the swing hammer head includes a hammer handle 1, a swing hammer head 2, a honeycomb ceramic preform 3 and an assembly fixing hole 4, wherein the swing hammer head 2 is installed and fixed at the end of the hammer handle 1, the upper end of the hammer handle 1 is provided with an assembly fixing hole 4, and the honeycomb ceramic preform 3 is installed at the end of the swing hammer head 2.

[0101] Figure 5 This is the actual picture of the working surface of the composite swing hammer after color flaw detection.

[0102] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for manufacturing a highly wear-resistant composite swing hammer head, characterized in that: The following steps are involved: S1: Ceramic particles with a particle size of 10 to 16 mesh are soaked in oxalic acid solution, vibrated and cleaned, and then placed in a drying oven for drying until the moisture on the surface of the ceramic particles is removed; S2: 300-400 mesh boron carbide ceramic powder and alcohol adhesive are uniformly mixed in proportion to form a slurry; S3: coating the slurry prepared in step S2 on the surface of the dried ceramic particles, and then drying them in a drying oven to remove the alcohol adhesive; S4: the ceramic particles prepared in step S3 are uniformly mixed with NiCrBSi powder and sodium silicate solution in proportion, and the mixed mixture is filled into a honeycomb mold, and then the whole is put into a microwave oven for microwave curing for a predetermined time and then taken out to obtain a honeycomb ceramic preform with high strength at room temperature, and the honeycomb ceramic preform is formed with conical preformed holes; S5: preheating the honeycomb ceramic preform to a preset temperature and then placing it into a casting cavity of a swing hammer metal mold, with the side with a larger preformed hole diameter close to the end face of the swing hammer; S6: installing the entire forming mold device of step S5 on a press, then pouring molten high-chromium cast iron into the pouring channel of the casting mold, and then closing the upper and lower molds and locking them under high pressure; S7: Under high pressure, the guide device is pushed to squeeze the high chromium cast iron liquid in the runner into the casting cavity of the swing hammer head mold, and the high chromium cast iron liquid is infiltrated into the gaps between the ceramic preform particles under high pressure to form a reactive interface, and the pressure is maintained until solidification is completed, and then the guide device is removed, and the mold is opened to eject the high wear-resistant composite swing hammer head blank; S8: cleaning and grinding the composite swing hammer head blank, and then putting it into a heat treatment furnace for quenching and tempering heat treatment to obtain a highly wear-resistant composite swing hammer head; In step S2, the amount of boron carbide ceramic powder added is 6% to 10% of the mass of the ceramic particles, and the amount of alcohol adhesive added is 8% to 12% of the mass of the ceramic particles; The surface of the ceramic particles is preferentially coated with boron carbide ceramic powder, and sufficient interface reaction bonding is achieved under high temperature when pouring high-chromium cast iron liquid; NiCrBSi powder can induce the infiltration of high chromium cast iron matrix and form infiltration channels.

2. The method for manufacturing a highly wear-resistant composite swing hammer head according to claim 1, characterized in that: In step S4, the amount of NiCrBSi powder added is 3% to 6% of the mass of the ceramic particles, and the amount of sodium silicate solution added is 6% to 9% of the mass of the ceramic particles.

3. The method for manufacturing a highly wear-resistant composite swing hammer head according to claim 1, characterized in that: The ceramic particles in step S1 are composed of aluminum oxide, zirconium oxide or zirconium corundum.

4. The method for manufacturing a highly wear-resistant composite swing hammer head according to claim 1, characterized in that: The mass content of oxalic acid in the oxalic acid solution in step S1 is 10% to 15%.

5. The method for manufacturing a highly wear-resistant composite swing hammer head according to claim 1, characterized in that: The alcohol adhesive in step S2 is ethanol, ethylene glycol or polyvinyl alcohol.

6. The method for manufacturing a highly wear-resistant composite swing hammer head according to claim 1, characterized in that: In step S4, the particle size of NiCrBSi powder is 300-400 mesh.

7. The method for manufacturing a highly wear-resistant composite swing hammer head according to claim 1, characterized in that: In step S6, the high chromium cast iron composition is BTMCr15, BTMCr20 or BTMCr26.

8. The method for manufacturing a highly wear-resistant composite swing hammer head according to claim 1, characterized in that: The preformed holes of the honeycomb ceramic preform are of a conical structure, and the taper of the preformed holes is 3° to 6°.

9. The method for manufacturing a highly wear-resistant composite swing hammer head according to claim 1, characterized in that: The honeycomb ceramic preform is arranged on a side of the swing hammer away from the hammer handle, and the thickness of the honeycomb ceramic preform is 25-40 mm.

Citation Information

Patent Citations

  • Functionally-graded wear-resistant iron-based composite material and preparation method thereof

    CN105817605A

  • Method for preparing aluminum oxide-based ceramic particle preform

    CN109095899A

  • Manufacturing method of metal ceramic composite swinging hammer

    CN112846192A

  • Preparation method of high-chromium cast iron-based ceramic composite grinding roller

    CN113579208A

Cited By

  • Gradient hardness composite ceramic swinging hammer and preparation method thereof

    CN121607602A

  • A gradient hardness composite ceramic drop hammer and a preparation method thereof

    CN121607602B